Flavonoids Inhibit Cancer by Regulating the Competing Endogenous RNA Network - Li, Chengshun; Li, Xiaolan; Jiang, Ziping; Wang, Dongxu; Sun, Liqun; Li, Jiaqi; Han, Yang (Frontiers in Oncology, 2022)
Flavonoids are present in a wide range of plants. They have been used in the treatment of cancer, but the mechanism underlying this activity is unclear. In recent years, microRNA (miRNA) and long non-coding RNA (lncRNA) levels have been observed to differ between normal tissues and cancer cells, and both types of RNA have been shown to have a role in tumor treatment. In addition, flavonoids have been proven to regulate miRNAs and LncRNAs in the treatment of cancer. The competing endogenous RNA (ceRNA) network is a complex post-transcriptional regulatory mechanism in cells, in which coding and non-coding RNAs competitively bind miRNAs to regulate messenger RNAs (mRNAs). This review focused on the role of the ceRNA network in the treatment of cancer by flavonoids.